Breaking free: motivating mathematics through escape rooms - Woolley, Thomas (MSOR Connections, 2025)
Escape rooms provide a unique and engaging way to promote mathematical thinking by embedding problems within a narrative-driven environment. This opinion piece highlights the effectiveness of escape rooms as a pedagogical tool, their ability to foster problem-solving skills, teamwork, and motivation among students. The study details the design principles used to create mathematical escape rooms, incorporating puzzles that require keen observation, logical reasoning and pattern recognition. Practical considerations, such as difficulty scaling and accessibility, are discussed, ensuring these activities cater to a diverse audience. By presenting mathematics in an immersive and interactive format, escape rooms encourage exploration and perseverance, ultimately improving students' confidence in tackling mathematical challenges.